Evaluation of the Therapeutic Effect of Adjuvant Transcatheter Arterial Chemoembolization Based on Ki67 After Hepatocellular Carcinoma Surgery - Zhao, Yu-Fei; Xiong, Xiu; Chen, Kai; Tang, Wei; Yang, Xu; Shi, Zheng-Rong (Frontiers in Oncology, 2021)
background and aims: This study aimed to determine the relationship between Ki67 expression and the efficacy of postoperative adjuvant transcatheter arterial chemoembolization (PA-TACE) in patients with liver cancer. Methods: the Kaplan-Meier method was used to analyze the recurrence-free survival (RFS) and overall survival (OS) rates between the sub-groups in the ki67 low expression group and the ki67 high expression group and analyze the relationship between the expression of Ki67 and the efficacy of TACE. Results: After PSM, there was no significant difference in the RFS and OS between the surgery + TACE and surgery subgroups after 1, 2, or 3 years (RFS: 62.5%, 52.5%, and 45.0% vs. 80.0 %, 60.0%, and 52.5%, respectively, P=0.367; OS: 90%, 77.5%, and 70% vs. 92.5%, 87.5%, and 67.5%, respectively, P=0.887) in the Ki67 low-expression group. The RFS and OS were higher in the surgery + TACE subgroup than the surgery subgroup after 1, 2, and 3 years (RFS: 80%, 76.9%, and 69.2% vs. 52.3%, 38.6%, and 30.2%, respectively, P˂0.001; OS: 97.5%, 84.6%, and 79.5% vs. 77.3%, 47.7%, and 41.9%, respectively, P<0.001) in the Ki67 high expression group. Conclusions: For patients with liver cancer and high expression of Ki67 (Ki67≥20%), adjuvant hepatic artery chemoembolization after radical liver tumor resection effectively reduced the probability of tumor recurrence after surgery and prolonged the OS of patients. High Ki67 expression during the post-operative follow-up evaluation of liver cancer patients is an indicator for adjuvant TACE therapy.